Emerging insights into the role of ferroptosis in the pathogenesis of autoimmune diseases - Fan, Junyu; Jiang, Ting; He, Dongyi (Frontiers in Immunology, 2023)
Ferroptosis, a novel type of regulated cell death mediated by iron-dependent lipid oxidation, was discovered a decade ago. Significant progress has been made in our knowledge of ferroptosis and immune dysfunction. This review covers recent advancements in the interaction of ferroptosis and the immune system, with an emphasis on autoimmune diseases. The critical regulators of ferroptosis are summarized in the context of reactive oxygen species biology, lipid metabolism, and iron homeostasis. The molecular crosstalk between ferroptosis and different immune cells is also highlighted. Future research is expected to yield new insights into the mechanisms governing ferroptosis and its potential therapeutic benefits in autoimmune diseases.